2014
DOI: 10.1111/jcpt.12162
|View full text |Cite
|
Sign up to set email alerts
|

Parkinsonism and severe hypothyroidism in an elderly patient: a case of lithium toxicity due to pharmacological interactions

Abstract: Lithium toxicity may present with concurrent hypothyroidism and parkinsonism. In the present case, interaction with valsartan and hydrochlorothiazide most likely played an important role. In patients who receive chronic therapy with lithium, prescribers should monitor lithium serum concentration both periodically and immediately at the onset of signs and symptoms, potentially related to lithium toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Moreover, both human and animal studies have reported that chronic lithium treatment itself is able to induce parkinsonian pathological features such as neuronal apoptosis in basal ganglia structures and impaired motor coordination [168][169][170]. Similar motor deficits and neuronal apoptosis are also induced in mice lacking GSK-3 or in cell cultures treated with other inhibitors of GSK-3 inhibitors such as indirubin-3 -monoxime, kenpaullone, and rottlerin, indicating that lithium induced Parkinsonism is mediated through GSK-3 inhibition [171,172].…”
Section: Gsk-3␤ Inhibition As a Therapeutic Potential For Pdmentioning
confidence: 99%
“…Moreover, both human and animal studies have reported that chronic lithium treatment itself is able to induce parkinsonian pathological features such as neuronal apoptosis in basal ganglia structures and impaired motor coordination [168][169][170]. Similar motor deficits and neuronal apoptosis are also induced in mice lacking GSK-3 or in cell cultures treated with other inhibitors of GSK-3 inhibitors such as indirubin-3 -monoxime, kenpaullone, and rottlerin, indicating that lithium induced Parkinsonism is mediated through GSK-3 inhibition [171,172].…”
Section: Gsk-3␤ Inhibition As a Therapeutic Potential For Pdmentioning
confidence: 99%
“…For instance, cardiovascular diseases, metabolic syndrome, and obesity, closely associated with hypertension, may be more prevalent among individuals with mania. These comorbid factors could be associated with the occurrence and severity of manic episodes and can impact treatment response (Basile et al, 2014;Liu et al, 2022). Moreover, some commonly applied antihypertensive medications may interfere with neural regulation and metabolic processes in individuals with mania, leading to exacerbation of manic symptoms or difficulties in their control (Colbourne et al, 2021;Yasui-Furukori and Fujii, 2013).…”
Section: O N L I N E F I R S T a R T I C L Ementioning
confidence: 99%